Sistem Kendali Gimbal 2-Sumbu Sebagai Tempat Kamera Pada Quadrotor Menggunakan PID Fuzzy - M Saiful Haris; Andi Dharmawan; Catur Atmaji (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2017)
The function of camera gimbal control system that use in this research is to serves with the angle changes that occur due quadrotor maneuver. The PID control with tuning classical method has weakness, which is the PID variable not independently adjust to the environment, thus proposed using PID fuzzy control.Gimbal camera used in this study has a mechanical design with two joint (pitch and roll) and the BLDC motor as actuator. The angle changes that occur in the pitch and roll axis will be a feedback system. Then, fuzzy logic will tune the PID variable based on that feedback.Results of testing the system on 2-axis gimbal camera shows the PID fuzzy control generates better response in parameter risetime, overshoot, and settlingtime compared with PID control. Error input value range of [-30° 30°] and delta error of [-10° 10°] on the pitch and roll axes. The range of the output value for the pitch axis is, Kp at [40.2 46.2], Ki at [10.7 20.7], and Kd of [0.05 to 0.15]. The range of the output value for the roll axis is, Kp at [6.4 16.4], Ki at [17.3 to 27.3], and Kd at [0.08 0.16]. Speed response speed of pitch axis is 0.12 second and the roll axis is 1.07 seconds.